Keynesianism and public investment. a left-Keynesian perspective on the role of goverment expenditures and debt. Mario Seccareccia - Seccareccia, Mario (Ontario, Can : Board, 1995)
Se analiza desde el punto de vista del Keynesianismo el papel del gobierno en el gasto público y la deuda
Keywords: ECONOMIA; POLITICA ECONOMICA; GASTO PÚBLICO; ESTADO BENEFACTOR